Kajian pelu dan tidaknya penambahan term Budi Pekerti dalam konten buku Pendidikan Agama Islam dan Budi Pekerti untuk siswa SMU - Ashar, Salim (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2017)
Character is a complicated issue, even considered an abstract problem. It is said to be abstract because the concept of manners is not yet operational. While good and bad standards for morals are in the objective view of God the Creator of man. If the character is ethics, it is very dangerous, because some of its value will be contrary to the moral lessons that exist in religious subjects. When both are taught (ethics and morals) then the threat is the students will later experience what is called a split personality, that is split personality. Students become confused because there are conflicting values, such as good values ​​in the sense of morals and good value in manners (call: ethics). There is no honest terminology of Arabic versions, honest English versions, false witnesses of Arabic and French versions, as there is no terminology about Arab or Turkish morality. This applies to humans when there is a pattern of intersection between ethical values ​​and customs: ethical values ​​derive from the "right" way (revelation), whereas customs are derived from the habits The purpose of this study are: 1) Describing whether or not the addition manners in the lessons of Islamic Religious Education. 2) Describe the material (content) in the lesson of Islamic Education and the intersection of Budi Pekerti based on traditional perspectives. This study uses "Library Research". The research data used is secondary data. Data collection techniques used are documentation. Data processing is done by conducting the activity of review, verification and reduction, grouping and systematization, and interpretation or interpretation so that a phenomenon has social, academic, and scientific value. From the results of the discussion concluded: 1) Based on the perspective of Islam, the lessons of Islamic Religious Education need not be added with the character, because in fact holistic education includes in the Islamic Religious Education. 2) The content of Islamic Religious Education should include aspects of Islam, ie Aqidah, Shari'ah and Akhlak which are taught in a balanced way, but the lesson of character can be combined as long as the adat is the custom of the Muslims.